Primary Nondural Central Nervous System Marginal ZoneB-Cell Lymphoma of the Mucosa-Associated Lymphoid Tissue Type Mimicking CNS Inflammatory Diseases. Issue 8 (8th September 2021) - Sugita, Yasuo; Hashimoto, Go; Fukuda, Kenji; Takahashi, Kenji; Shioga, Taro; Furuta, Takuya; Arakawa, Fumiko; Ohshima, Koichi; Nakamura, Hideo; Miyata, Hajime; Watanabe, Masashi; Kakita, Akiyoshi
Abstract: Marginal zone B-cell lymphomas (MZBCLs) are non-Hodgkin lymphomas arising from postgerminal center marginal zone B cells. MZBCLs are subclassified into extranodal, nodal, and splenic MZBCLs. Primary nondural central nervous system (CNS) MZBCLs of the mucosa-associated lymphoid tissue (MALT) type are among the extranodal examples. Their clinicopathological features are not well characterized. Therefore, the clinicopathological features of 8 primary nondural CNS MZBCLs of the MALT type were assessed to establish their pathological diagnostic criteria. Histologically, all cases of primary nondural CNS MZBCLs of the MALT type showed perivascular expansive monotonous proliferation of small atypical B lymphoid cells with plasma cell differentiation, low Ki-67 labeling index, and minimal invasion from the perivascular space. In addition, no vascular changes such as glomeruloid changes, obliterative fibrointimal proliferation, and intramural lymphocytic infiltration were seen. These key histological characteristics should be considered when diagnosing cases that are suspected to be primary nondural CNS MZBCLs of the MALT type. Additionally, regarding PCR for the detection of immunoglobulin heavy variable gene and T-cell receptor γ gene rearrangements, the former is detected, but the latter is not detected in all cases. Therefore, PCR detection including sequence analysis should be added when diagnosing difficult cases based on the key histological characteristics.